Foreign Direct Investment Opportunity for Modified Cassava Starch in Indonesia - Respati Wulandari; Gita Amanda; Reynaldo Damara Salim (Bina Nusantara University, 2021)
Modified cassava starch is widely used in a range of applications such as food and beverage, papermaking, textiles, chemicals, constructions, adhesives, and pharmaceuticals. Hence, there is a massive demand for modified cassava starch in Indonesia. Nowadays, in the agricultural sector, our production capacity is only 1% of the total demand and this means that there are not many modified starch plantations in Indonesia. The aim of this research is to identify the external and internal factors that influence the foreign direct investment potential of modified cassava starch in Indonesia.